Personality Traits and Ethical Belief as Factors Influencing Fraud Intent Behaviour among Bank Employees in Ibadan, Nigeria. - Ajibola Abdulrahamon Ishola; Akeem Adekunle Kenku; Olufunmilayo Adedayo (TIJAB (The International Journal of Applied Business), 2021)
Fraud is an ever-growing problem for financial institutions in Nigeria, with criminals using a wide variety of methods. Unfortunately, employees were fingered in most of these fraudulent activities. Previous studies focused on contextual and organizational antecedents of motivating engagement in fraudulent practices and less on employees’ dispositional factors. This study examined the role of personality traits and ethical beliefs on fraudulent behaviour among bank employees. The study was a cross-sectional study. Three hundred and fifty-three (353) employees in the middle to junior level management cadre were selected through stratified sampling technique from banking organisations operating in the Ibadan metropolis. The respondents responded to a self-report questionnaire measuring fraudulent behaviour intention and red flags; personality traits and Ethical position questionnaire. Two hypotheses were tested using multiple regression, Pearson correlation analysis and ANOVA at p≤0.05. Results demonstrated that conscientiousness personality trait was the only predictor of fraud intent behaviour among the personality variables. Employees with Absolutist ethical principles reported lower fraud intent behaviour than those with subjectivist ethical philosophy. The study concludes that personality traits and ethical beliefs were powerful motivators for fraud behavior. Thus, fraud and HR experts were enjoined to utilize psychological profiles in fraud investigations and selection of employees.